Analysis of PT. Freeport Indonesia internal csr programs towards alexander dahlsrud and geoffrey lantos theory - Ramadhianto, Rizqi Dwi; Rudito, Bambang (Journal of Business and Management, 2019)
Abstract. Corporate Social Responsibility (CSR) has been known as an activity of a company to maintain good relations with their employee, local communities and government. It is also an act of contribution towards environment. The purpose of CSR is to create a sustainable business. Every company has their own CSR programs and their consideration on creating it. Therefore, this research tries to analyse frameworks of PT. Freeport Indonesia CSR program towards Alexander Dahlsrud and Geoffrey Lantos definition of CSR. Alexander Dahsrud created a CSR dimension that consist of 5 dimension which are environment, social, economic, stakeholder, and voluntaries. Geoffrey Lantos also created a CSR dimension that consist of 3 dimension which are ethical, altruistic, and strategic. The purpose of this research is to compare PT. Freeport Indonesia towards Alexander Dahlsrud and Geoffrey Lantos concept of CSR. Expectantly, this research will help PT. Freeport Indonesia on conducting further CSR programs. This research uses qualitative approach with several departments of PT. Freeport Indonesia and minor quantitative approach by crosschecking with PT. Freeport Indonesia CSR reports. From the findings, author knew frameworks used by PT. Freeport Indonesia are International Council on Mining and Metals: Sustainable Development and International Organization for Standardization 26000. Furthermore, author found that those frameworks have similarity towards Alexander Dahlsrud and Geoffrey Lantos CSR dimensions.Key words: CSR, ICMM, ISO 26000. Alexander Dahlsrud, Geoffrey Lantos